Bridging the Gap: Technology and Veteran Academic Success - Cass, David; Hammond, Shane (Online Learning, 2014)
This paper presents two unique yet confluent perspectives regarding the use of technology to support student veterans in college, and is meant to ignite discussion of the blending of high impact practices with technology to promote their academic success. The authors highlight the historical trends of student veterans in the academy and discuss the barriers to success for this unique population of students. Uvize, an online mentoring and advising platform for student veterans, is introduced with an overview of the creation of the program and preliminary results from three forward thinking institutions. This article further defines why student veterans are a special student population on our campuses and require unique services to support their overall academic success. Theoretical and pragmatic technology based solutions for student veteran successes are presented.